Design and Development of Smart Pedestrian Lighting System in UNITEN - Chua , Yaw Long; Mohd Suhaimi, Amirul Syahmi Aiman; Yit Yan, Koh (Journal of Advanced Research Design, 2025)
This project addresses energy wastage from continuous lighting in university walkways, particularly during low foot traffic after 10 pm, by implementing a Smart Pedestrian Lighting System. This system integrates an Arduino microcontroller, various sensors, and an IoT cloud. The lights operate under normal conditions from 7 am to 7 pm, activating only when ambient light is low. From 7 pm to 10 pm, the lights stay on continuously. After 10 pm, the system uses PIR motion sensors and LDR to illuminate the pathway as needed. All data collected is transmitted to the IoT cloud via the UNITEN Wi-fi for real-time monitoring and assessment. Two prototypes, Pro1 and Pro2, were developed and evaluated. Pro1 includes six LEDs, seven 1k omega resistors, one LDR, six PIR sensors, one ESP-01s, one RTC module, and an Arduino R3 board. Pro2 has similar components but uses an Arduino R4 WIFI board. The results showed that Pro2 is more reliable, effectively addressing high energy consumption and carbon emissions. Stark contrast in energy usage and CO2 emission was obtained as compared to the existing setup. The Smart Lighting System can contribute to the university effort to become a Smart Campus, providing a potential positive step towards energy saving strategies and achieving UNSDG.